Orbital volume measurements from magnetic resonance images using the techniques of manual planimetry and stereology - Bontzos, Georgios; Mazonakis, Michael; Papadaki, Efrosini; Maris, Thomas; Blazaki, Styliani; Drakonaki, Eleni; Detorakis, Efstathios (National journal of maxillofacial surgery, 2020)
Introduction: Current volume measurement techniques, for the orbit, are time-consuming and involve complex assessments, which prevents their routine clinical use. In this study, we evaluate the applicability and efficacy of stereology and planimetry in orbital volume measurements using magnetic resonance imaging (MRI). Materials and Methods: Prospective imaging study using MRI. Sheep craniums and human subjects were evaluated. Water-filling measurements were performed in animal skulls, as the standard validation technique. Planimetry and stereology techniques were used in each dataset. Intraobserver and interobserver reliability testing were applied. Results: In stereology customization, 1/6 systematic sampling scheme was determined as optimal with acceptable coefficient of error (3.09%) and low measurement time (1.2 min). In sheep craniums, the mean volume measured by water displacement, planimetry, and stereology was 17.81 ± 0.59 cm3, 18.53 ± 0.24 cm3, and 19.19 ± 0.17 cm3, respectively. Planimetric and stereological methods were highly correlated (r = 0.94; P ≈ 0.001). The mean difference of the orbital volume using planimetry and stereology was 0.316 ± 0.168 cm3. In human subjects, using stereology, the mean orbital volume was found to be 19.62 ± 0.2 cm3 with a CE of 3.91 ± 0.15%. Conclusions: The optimized stereological method was found superior to manual planimetry in terms of user effort and time spent. Stereology sampling of 1/6 was successfully applied in human subjects and showed strong correlation with manual planimetry. However, optimized stereological method tended to overestimate the orbital volume by about 1 cc, a considerable limitation to be taken in clinical practice.